1999
DOI: 10.1002/(sici)1097-4636(1999)48:2<172::aid-jbm12>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Vascular graft healing: I. FTIR analysis of an implant model for studying the healing of a vascular graft

Abstract: FTIR analysis of sequential biopsy samples of the primary and replacement segments obtained from 70 to 80-cm long carotid-femoral bypass grafts implanted bilaterally in the dog indicate that the healing pattern is similar over the entire length of these grafts. Preliminary analysis of the spectra also indicates that the major developments in the formation of the biological layer appear to occur during the first 4 weeks after implantation. Collagen IV could be detected by both FTIR and antibody staining in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Amide I band can be used for the determination of protein secondary structure as the frequency of vibrations of this band is sensitive to protein conformation [21,22,29]. The results of this study indicate a very slight shift to lower values observed in the frequency of amide I band in diabetic group of EDL muscle (Table 2).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Amide I band can be used for the determination of protein secondary structure as the frequency of vibrations of this band is sensitive to protein conformation [21,22,29]. The results of this study indicate a very slight shift to lower values observed in the frequency of amide I band in diabetic group of EDL muscle (Table 2).…”
Section: Resultsmentioning
confidence: 67%
“…The spectra were normalized with respect to the amide A band. Table 1 General band assignment of FTIR spectrum of skeletal muscle tissue based on literature [11,12,15,14,[19][20][21][22] Peak No.…”
Section: Resultsmentioning
confidence: 99%
“…This band can be assigned as the PO 2 − symmetric stretching band arising from phospholipids [31] or due to the C-O stretching band which mainly arises from glycogen, oligosaccharides and glycolipids present in the system [29,32]. Figure 5 also illustrates the presence of a sharp band at 1041 cm −1 , originating from the various C-O stretching vibrations characteristic for polysaccharides [33]. It is possible to observe a slight increase in the intensity of this band in all the diabetic groups.…”
Section: The 1000-1270 CM −1 Regionmentioning
confidence: 94%
“…Table 1. Table 1 Main ATR FT-IR (1200-1800 cm −1 ) peak positions determined from the minima of the second derivative spectra of: (a) G. melastomus egg case (this work), (b) collagen IV (this work) and, also, ATR FT-IR absorption band maxima from: (c) collagen IV from vascular graft [28], (d) aqueous solution of collagen IV from human placenta [26], (e) aqueous solution of collagen IV from human placenta [27] Dogfish egg case collagen, this work Powder collagen IV from human placenta, this work Collagen IV from vascular graft [28] Aqueous solution of collagen IV [26] Aqueous solution of collagen IV [27] Assignments-comments When compared in the second derivative formalism, collagen IV and the DEC specimens, white or brown, outer or inner, exhibit many similarities in the amide I, II and III regions, suggesting the existence of common secondary structural characteristics. In all spectra, the strongest amide I band is observed at 1630 cm −1 and is accompanied by a number of weaker components at higher frequencies (Fig.…”
Section: Atr Ft-ir Spectroscopymentioning
confidence: 99%